Gastrointestinal blood flow velocity after the first feed. Issue 1 (January 1991) - Gladman, G; Sims, D G; Chiswick, M L
Abstract : Twenty preterm infants (gestational age range 27-36 weeks) who had never been fed enterally were studied. Doppler indices of flow velocity from the superior mesenteric and coeliac arteries were measured immediately before, and at postprandial time intervals up to 60 minutes after, a first feed of 1 ml of milk given through a nasogastric tube. There were no significant differences between the preprandial and postprandial values of blood pressure, heart rate, oxygen and carbon dioxide tensions, and pH. The median peak systolic velocity (PSV) (55.9 cm/sec) and time average mean velocity (TAV) (10.6 cm/sec) before the feed at the superior mesenteric artery rose progressively and significantly to postprandial peaks of 88.5 cm/sec and 20.5 cm/sec at 45 minutes, respectively. Significant postprandial rises in the median PSV and TAV values at the coeliac artery were also observed, with a peak at 45 minutes. There were no significant correlations between blood flow velocity indices (preprandial or postprandial) and gestational age, postnatal age, conceptional age, or birth weight. We conclude that the first exposure of preterm babies to a small volume of milk feed is associated with postprandial changes in blood flow velocity consistent with an increase in blood flow in the superior mesenteric and coeliac arteries, although the mechanism of this response is uncertain.